Rapid and non-destructive nanofiber diameter measurement using Spontaneous Four Wave Mixing - Bridonneau Aglaé; Weng Ruiling; Shi Mingzhao; Dupuis Christophe; Coutrot Anne-Lise; Delaye Philippe; Lebrun Sylvie (EPJ Web of Conferences)
We will present a rapid and non-destructive technique for the measurement of the mean diameter of a silica nanofiber using the wavelength position of the signal peak in a spontaneous four wave mixing experiment. The nanofiber diameter can be characterized in a range going at least from 650 to 1250nm. Several nanofibers were characterized, and the measured diameter show a good accordance with the one obtained using a Scanning Electron Microscope. The technique is simple to use and has even the potential to be implemented in situ in order to realize a diameter measurement during the pulling of the nanofiber for a better control of the final diameter of the nanofiber.